STRATEGI GURU MENUMBUHKAN MINAT BELAJAR PESERTA DIDIK MENGGUNAKAN ALAT PRAGA PADA MATERI PENGARUH GAYA TERHADAP BENDA DI KELAS IV SD NEGERI 6 PENINJOAN TEMBUKU BANGLI (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Learning strategies can be understood as a method, a set of methods, techniques that are carried out and taken by a teachers or students in to make a change in behavior or attitude. One of the subjects in elementary schools that requires a deeper concept understanding to get optimal learning outcomes is Science subjects. In Science learning processes, teachers should manage learning media well. The problems studied are as follows: (1) How are the Teachers' Strategy to Grow Students' Interest in Learning Using Props on Influence of Style to Objects subject in Class IV State Elementary School 6 Peninjoan Tembuku Bangli, (2) What are the obstacles faced by teachers in Teacher Strategy Growing Learning Interests of Students Using Praga Tools on the Influence of Style on Objects in Class IV State Elementary School 6 Peninjoan Tembuku Bangli, (3) What efforts are made by teachers to overcome obstacles in Cultivating Students' Interest in Learning Using Praga Tools on Materials for Effects of Force on Objects in Class IV State Elementary School 6 Peninjoan Tembuku Bangli. The theories used in this study are: Behavioristic Theory according to Gagne 201, Cognitive learning theory according to Given 2014, According to the theory of encouragement or motivation according to C. Chifford Morgan 2005. Data obtained by observation, interviews, literatures, documents, data analysis techniques in This study was analyzed by qualitative descriptive data analysis, namely the data described from beginning to end in words, and the results of data analysis techniques. The results obtained in this study are: (1) The teacher's strategy to foster student interest in learning using Props on the material of the influence of style on objects in class IV State of Elementary School 6 Peninjoan Tembuku Bangli uses two methods in learning, namely: the experimental method, the play method (2 ) The obstacles faced by teachers in fostering student interest in learning using Props on the material of the influence of style on objects in class IV State Elementary School 6 Peninjoan Tembuku Bangli are caused by two obstacles, namely: Internal constraints and External Constraints that come from outside the students. (3) Efforts made by teachers in fostering student interest in learning using praga tools on the material influence of style on objects in class IV State Elementary School 6 Peninjoan Tembuku Bangli are: Approaching Students, Innovating in Learning, Optimizing the Use of Learning Media.